Ceramic shell back layer slurry for single crystal blade as well as preparation method and application of ceramic shell back layer slurry
By optimizing the formulation and process of the ceramic shell backing slurry, the problems of hot cracking and recrystallization in the casting of multi-unit single-crystal guide vanes and crowned blades were solved, and the high-temperature collapsibility and disintegration properties were improved, meeting the precision casting requirements of single-crystal turbine blades for aero-engines.
Patent Information
- Application Number
- CN202511139075.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-18
AI Technical Summary
Existing ceramic shell materials have problems such as poor fluidity of the back layer slurry and excessive residual strength of the shell leading to hot cracking and recrystallization during the casting process of multi-unit single-crystal guide blades and crowned blades, which affect the yield and quality stability of the blades.
A ceramic shell backing slurry with a specific formulation, including fused white corundum powder, fused mullite powder and fused silica powder, is prepared by adding appropriate amounts of organic additives such as wetting agents, defoamers and thickeners, and by optimizing the powder particle size distribution and mixing process, a ceramic shell with good flowability and collapsibility is prepared, and the residual strength is reduced.
It significantly improves the fluidity of the backing slurry, avoids hot cracking and recrystallization defects, meets the usage requirements of multi-unit single-crystal guide vanes and crowned vanes, and improves casting quality and stability.
Smart Images

Figure BDA0005549025380000131 
Figure HDA0005549025390000011 
Figure HDA0005549025390000021
Abstract
Description
Technical Field
[0001] This invention belongs to the field of precision casting technology for single-crystal blades, and relates to a ceramic mold shell backing layer slurry for single-crystal blades and its preparation method, a ceramic mold shell for casting single-crystal blades, and its application, especially to a ceramic mold shell backing layer slurry for single-crystal blades and its preparation method, and its application. Background Technology
[0002] With the continuous development of high thrust-to-weight ratio aero-engines, turbine inlet temperatures are increasing, and the operating conditions of turbine blades are becoming increasingly demanding. This has spurred milestone changes in the material selection and structural design of turbine blades for aero-engines. During this period, turbine blade materials have evolved from equiaxed cast superalloys and directionally solidified columnar superalloys to single-crystal superalloys, and turbine blade structural designs have also evolved from simple solid structures to air-cooled multi-cavity hollow structures. Currently, single-crystal superalloys possess excellent high-temperature comprehensive performance and are the preferred materials for manufacturing hollow turbine blades for advanced aero-engines; for complex multi-stage single-crystal guide vanes, the ceramic shell used in their precision casting is a crucial material.
[0003] The quality of the ceramic shell directly affects the surface quality and dimensional accuracy of turbine blades. With continuously increasing casting temperatures and more complex casting conditions, increasingly stringent requirements are being placed on the performance of ceramic shells. An excellent ceramic shell should meet performance requirements such as good room temperature strength, high temperature strength, permeability, thermal expansion, thermal shock stability, thermochemical stability, thermal conductivity, collapsibility, and collapse resistance. Ceramic shells are manufactured through a layer-by-layer coating process. While the surface layer of the shell determines its thermochemical stability, the back layer determines key indicators such as high temperature strength, permeability, collapsibility, and collapse resistance.
[0004] Existing ceramic mold shells, due to their single material composition, fail to fully utilize the combined properties of each material, resulting in poor filling performance of the mold shell backing slurry. This leads to excessively high residual strength after directional solidification, resulting in poor high-temperature resilience and making them prone to recrystallization defects in multi-unit single-crystal guide vanes and crowned vanes (such as...). Figure 1 and Figure 2 As shown in the figure, in severe cases, it can even cause thermal cracking in some blades in the large cross-section structure perpendicular to the heat flow direction, affecting the blade qualification rate and quality stability.
[0005] Therefore, finding a more suitable way to solve the aforementioned technical problems of existing ceramic shells used for precision casting of multi-crystal guide vanes has become one of the urgent problems to be solved by many front-line researchers in the industry. Summary of the Invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a ceramic shell backing slurry for single-crystal blades and its preparation method, a ceramic shell for casting single-crystal blades, and its application. The ceramic shell backing slurry for single-crystal blades provided by the present invention can significantly improve the fluidity of the backing slurry, while avoiding the thermal cracking and recrystallization problems caused by shell constraint in multi-unit single-crystal guide blades and crowned blades. Moreover, the preparation method is simple and easy to implement, with mild conditions, strong controllability, and good stability, making it more suitable for industrial promotion and application.
[0007] This invention provides a ceramic shell backing slurry for single-crystal blades, comprising, by raw materials: a mixed solution of binder and organic additives and a powder composed of ceramic powder;
[0008] The ceramic powder comprises 10wt% to 30wt% of fused white corundum powder, 70wt% to 90wt% of fused mullite powder, and 0wt% to 10wt% of fused silica powder.
[0009] The organic additives include one or more of wetting agents, defoamers, and reinforcing agents, as well as thickeners.
[0010] Preferably, the particle size of the fused white corundum powder is 0–0.12 mm;
[0011] The particle size of the electrofused mullite powder is 0–0.07 mm;
[0012] The particle size of the fused silica powder is 0–0.15 mm;
[0013] The powder to the mixed solution mass ratio is (2-4):1;
[0014] The flow cup viscosity of the ceramic shell backing slurry is 10–25 s.
[0015] Preferably, the amount of the reinforcing agent is 5% to 10% of the mass of the adhesive;
[0016] The amount of the thickener is 0.1% to 0.3% of the volume of the binder;
[0017] The amount of the wetting agent is 0.3% to 0.9% of the volume of the adhesive;
[0018] The amount of the defoamer is 0.3% to 0.9% of the volume of the adhesive;
[0019] The weight of the plate when the ceramic shell back layer slurry is coated is 0.03–0.05 g / cm³. 2 .
[0020] Preferably, the binder comprises silica sol;
[0021] The thickener includes one or more of associative polyurethane, hydroxymethyl cellulose, and hydroxymethyl starch;
[0022] The wetting agent includes wetting agent type V12 and / or wetting agent type 8M;
[0023] The defoamer includes n-octanol and / or defoamer Burst 100;
[0024] The reinforcing agent includes one or more of polyacrylic acid emulsion, polystyrene-acrylic emulsion, and polyethylene glycol.
[0025] This invention provides a method for preparing a ceramic shell backing slurry for single-crystal blades as described in any of the above technical solutions, comprising the following steps:
[0026] 1) After mixing fused white corundum powder, fused mullite powder and fused quartz powder, ceramic powder is obtained;
[0027] After the binder and organic additives are mixed again, a mixed solution is obtained;
[0028] 2) After initial mixing and secondary mixing of the ceramic powder and the mixed solution obtained in the above steps, a ceramic shell backing slurry is obtained.
[0029] Preferably, the mixing speed is 8–15 r / min;
[0030] The mixing time is 30–60 minutes;
[0031] The remixing time is 5–10 minutes;
[0032] The remixing speed is 100-300 r / min;
[0033] The initial mixing speed is 900–1500 r / min;
[0034] The initial mixing time is 2–6 hours;
[0035] The initial mixing temperature is 21–25°C;
[0036] The secondary mixing time is 48h to 72h.
[0037] The present invention provides a ceramic shell for casting single crystal blades, wherein the back layer of the ceramic shell is prepared by the ceramic shell back layer slurry described in any one of the above technical solutions or the ceramic shell back layer slurry obtained by the preparation method described in any one of the above technical solutions.
[0038] Preferably, the casting method includes precision casting;
[0039] The single-crystal blades include multi-unit single-crystal guide blades and / or multi-unit single-crystal crowned blades;
[0040] The preparation methods include coating and calcination;
[0041] The roasting temperature is 650–800°C.
[0042] This invention provides the ceramic shell backing slurry according to any one of the above technical solutions, the ceramic shell backing slurry obtained by the preparation method according to any one of the above technical solutions, or the application of the ceramic shell according to any one of the above technical solutions in the preparation of single crystal blades.
[0043] Preferably, the applications include those that reduce or avoid recrystallization defects and / or thermal cracking problems on the surface of single-crystal blades;
[0044] The application methods include reducing the residual strength of the ceramic shell and / or improving the high-temperature resilience of the ceramic shell;
[0045] In the process of preparing single-crystal blades, the ceramic shell is removed by alkaline boiling.
[0046] This invention provides a ceramic shell backing slurry for single-crystal blades, comprising, by raw materials: a mixed solution of binder and organic additives, and a powder composed of ceramic powder; the ceramic powder includes 10wt%–30wt% fused white corundum powder, 70wt%–90wt% fused mullite powder, and 0–10wt% fused silica powder; the organic additives include one or more of wetting agents, defoamers, and reinforcing agents, as well as a thickener. Compared with the prior art, this invention specifically designs a ceramic shell backing slurry for single-crystal blades with a specific formula and composition, which can significantly improve the flowability of the backing slurry, while also avoiding thermal cracking and recrystallization caused by shell constraint in multi-unit single-crystal guide blades and crowned blades. This invention, through ceramic powder particle size distribution, high-temperature performance adjustment, and the addition of appropriate amounts of organic additives, achieves excellent flowability and collapsibility. The residual strength of the shell prepared by this slurry can be reduced by more than 50%, meeting the requirements for use in multi-unit single-crystal guide blades and crowned blades.
[0047] This invention designs the shell material as a mixture of fused white corundum powder and fused mullite powder. The fused mullite is a standard 3Al2O3·2SiO2. During the directional solidification of the metal, the pre-added fused mullite acts as a seed crystal, promoting mullite formation and ensuring the high-temperature performance of the shell. The introduction of fused silica increases the SiO2 content of the entire shell system, improving the shell's collapse and yielding properties. Its residual strength is only 30% of that of pure fused white corundum shells and EC95 shells, alleviating the recrystallization tendency of multi-unit single-crystal guide vanes and crowned vanes. Moreover, the shell material can be removed by alkaline boiling, avoiding recrystallization of single-crystal vanes caused by physical removal.
[0048] This invention uses a mixture of fused white corundum, fused mullite, and fused silica powder as ceramic and refractory materials, silica sol as a binder, and appropriate organic additives to form a mixed solution. The process involves rapid stirring, stable stirring with an L-type mixer, and slurry adjustment. This invention optimizes the selection and particle size distribution of several ceramic powders and adds appropriate amounts of organic additives (wetting agents, defoamers, reinforcing agents, thickeners, etc.). In particular, the innovative introduction of thickeners significantly improves the coatability of the backing slurry. By combining the performance advantages of several ceramic powders in a specific ratio, the prepared shell exhibits excellent yielding properties, ensuring that the multi-unit single-crystal guide vanes and crowned blades do not suffer from residual stress due to excessive shell strength hindering metal shrinkage. This prevents recrystallization defects after heat treatment between multi-unit blades and at the blade / crown transition points, thus solving the surface recrystallization problem of multi-unit single-crystal guide vanes and crowned blades, and meeting the precision casting requirements for single-crystal turbine blades in aero-engines. Moreover, the preparation method is simple and easy to implement, the conditions are mild, the controllability is strong, and the stability is good, making it more suitable for industrial promotion and application. Attached Figure Description
[0049] Figure 1 A simplified schematic diagram of recrystallization for the multi-unit single-crystal guide vane provided by the present invention;
[0050] Figure 2 A simplified schematic diagram illustrating recrystallization at the transition between the leaf margin / crown and leaf body, provided by the present invention. Detailed Implementation
[0051] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims.
[0052] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.
[0053] The purity of the raw materials used in this invention is not particularly limited. Preferably, the purity is analytical grade or conventional in the field of manufacturing ceramic shells for single-crystal blades.
[0054] All raw materials of this invention are conventional in the field, and each brand name and abbreviation is clear and distinct in its relevant application. Those skilled in the art can purchase them from the market or prepare them by conventional methods based on the brand name, abbreviation and corresponding application.
[0055] All processes in this invention are referred to by abbreviations that are common abbreviations in the field. Each abbreviation is clear and specific in its relevant application area, and those skilled in the art can understand its conventional process steps based on the abbreviation.
[0056] This invention provides a ceramic shell backing slurry for single-crystal blades, comprising, by raw materials: a mixed solution of binder and organic additives and a powder composed of ceramic powder;
[0057] The ceramic powder comprises 10wt% to 30wt% fused white corundum powder, 70wt% to 90wt% fused mullite powder, and 0wt% to 10wt% fused silica powder.
[0058] The organic additives include one or more of wetting agents, defoamers, and reinforcing agents, as well as thickeners.
[0059] In this invention, the sum of the percentage content of the components in the ceramic powder is 100%.
[0060] In this invention, the amount of fused white corundum powder added is 10wt% to 30wt%, or it can be 12wt% to 27wt%, or 15wt% to 25wt%, or 17wt% to 23wt%.
[0061] In this invention, the amount of fused mullite powder added is 70wt% to 90wt%, or it can be 72wt% to 87wt%, or 75wt% to 85wt%, or 77wt% to 83wt%.
[0062] In this invention, the amount of fused silica powder added is 0-10 wt%, which can be 0.01 wt%-9 wt%, 1 wt%-8 wt%, or 3 wt%-6 wt%.
[0063] In this invention, the particle size of the fused white corundum powder is preferably 0-0.12 mm, more preferably 0.01-0.12 mm, and even more preferably 0.02-0.08 mm.
[0064] In this invention, the particle size of the electrofused mullite powder is preferably 0 to 0.07 mm, more preferably 0.01 to 0.07 mm, and even more preferably 0.02 to 0.06 mm.
[0065] In this invention, the particle size of the fused silica powder is preferably 0 to 0.15 mm, more preferably 0.01 to 0.15 mm, and even more preferably 0.04 to 0.12 mm.
[0066] In this invention, the preferred powder-to-liquid mass ratio is (2-4):1, more preferably (2.2-3.8):1, even more preferably (2.5-3.5):1, and even more preferably (2.7-3.3):1.
[0067] In this invention, the flow cup viscosity of the ceramic shell backing slurry is preferably 10–25 s, more preferably 12–23 s, and even more preferably 15–20 s. Specifically, the flow cup is a No. 6 cup.
[0068] In this invention, the amount of the reinforcing agent is preferably 5% to 10% of the mass of the adhesive, more preferably 6% to 9%, and even more preferably 7% to 8%.
[0069] In this invention, the amount of the thickener is preferably 0.1% to 0.3% of the binder volume, more preferably 0.12% to 0.28%, more preferably 0.15% to 0.25%, and even more preferably 0.18% to 0.23%.
[0070] In this invention, the amount of the wetting agent is preferably 0.3% to 0.9% of the volume of the adhesive, more preferably 0.4% to 0.8%, and even more preferably 0.5% to 0.7%.
[0071] In this invention, the amount of the defoamer is preferably 0.3% to 0.9% of the volume of the binder, more preferably 0.4% to 0.8%, and even more preferably 0.5% to 0.7%.
[0072] In this invention, the preferred plate weight during the coating of the ceramic shell backing slurry is 0.03–0.05 g / cm³. 2 More preferably, it is 0.032–0.048 g / cm³. 2 More preferably, it is 0.035–0.045 g / cm³. 2 More preferably, it is 0.037–0.043 g / cm³. 2 .
[0073] In this invention, plate weight refers to the dry weight of the paste attached to a unit area of substrate (or carrier).
[0074] In this invention, the binder preferably comprises silica sol. Specifically, it can be GRJ-26 silica sol and / or GRJ-30 silica sol.
[0075] In this invention, the thickener preferably includes one or more of associative polyurethane, hydroxymethyl cellulose and hydroxymethyl starch, more preferably associative polyurethane, hydroxymethyl cellulose or hydroxymethyl starch.
[0076] In this invention, the wetting agent preferably includes wetting agent V12 type and / or wetting agent 8M type, more preferably wetting agent V12 type or wetting agent 8M type. The wetting agent is WETEKV12 from Remet Company (UK) or wetting agent 8M type from Tianjin Saifei Company, and its main component is polyethylene oxide.
[0077] In this invention, the defoamer preferably includes n-octanol and / or defoamer Burst 100, more preferably n-octanol or defoamer Burst 100. Specifically, the defoamer Burst 100 is Burst 100 from Remet Ltd., UK.
[0078] In this invention, the reinforcing agent preferably includes one or more of polyacrylic acid emulsion, polystyrene-acrylic emulsion, and polyethylene glycol, more preferably polyacrylic acid emulsion, polystyrene-acrylic emulsion, or polyethylene glycol.
[0079] This invention provides a method for preparing a ceramic shell backing slurry for single-crystal blades as described in any of the above technical solutions, comprising the following steps:
[0080] 1) After mixing fused white corundum powder, fused mullite powder and fused quartz powder, ceramic powder is obtained;
[0081] After the binder and organic additives are mixed again, a mixed solution is obtained;
[0082] 2) After initial mixing and secondary mixing of the ceramic powder and the mixed solution obtained in the above steps, a ceramic shell backing slurry is obtained.
[0083] The present invention first mixes fused white corundum powder, fused mullite powder and fused quartz powder to obtain ceramic powder;
[0084] The binder and organic additives are mixed again to obtain a mixed solution.
[0085] In this invention, the mixing speed is preferably 8 to 15 r / min, more preferably 9 to 14 r / min, and even more preferably 10 to 13 r / min.
[0086] In this invention, the mixing time is preferably 30-60 min, more preferably 35-55 min, and even more preferably 40-50 min.
[0087] In this invention, the mixing device is preferably a V-type mixer.
[0088] In this invention, the remixing time is preferably 5 to 10 minutes, more preferably 6 to 9 minutes, and even more preferably 7 to 8 minutes.
[0089] In this invention, the remixing speed is preferably 100-300 r / min, more preferably 120-280 r / min, more preferably 150-250 r / min, and even more preferably 170-230 r / min.
[0090] In this invention, the initial mixing speed is preferably 900-1500 r / min, more preferably 1000-1400 r / min, and even more preferably 1100-1300 r / min.
[0091] In this invention, the initial mixing time is preferably 2 to 6 hours, more preferably 2.5 to 5.5 hours, more preferably 3 to 5 hours, and even more preferably 3.5 to 4.5 hours.
[0092] In this invention, the initial mixing temperature is preferably 21-25°C, more preferably 22-24°C.
[0093] In this invention, the secondary mixing time is preferably 48h to 72h, more preferably 51h to 69h, and even more preferably 55h to 65h.
[0094] In this invention, the secondary mixing device is preferably an L-shaped stirrer.
[0095] Specifically, the preparation steps described above in this invention can be the following processes:
[0096] a) Place all ceramic powder into a V-type mixer and mix for 30-60 minutes at a speed of 8-15 r / min;
[0097] Initially mix silica sol, wetting agent, defoamer, reinforcing agent, etc. for 5-10 minutes at a speed of 100-300 r / min;
[0098] b) Add the ceramic powder to the mixed solution and mix for 2-6 hours at a speed of 900-1500 r / min;
[0099] c) After mixing, place the mixture in an L-shaped mixing device and continue mixing for 48 to 72 hours.
[0100] The present invention provides a ceramic shell for casting single crystal blades, wherein the back layer of the ceramic shell is prepared by the ceramic shell back layer slurry described in any one of the above technical solutions or the ceramic shell back layer slurry obtained by the preparation method described in any one of the above technical solutions.
[0101] In this invention, the casting method preferably includes precision casting.
[0102] In this invention, the single-crystal blade preferably includes multi-unit single-crystal guide blades and / or multi-unit single-crystal crowned blades, more preferably multi-unit single-crystal guide blades or multi-unit single-crystal crowned blades.
[0103] In this invention, the preparation method preferably includes coating and calcination.
[0104] In this invention, the roasting temperature is preferably less than or equal to 800°C, more preferably 650-800°C, more preferably 670-780°C, and even more preferably 700-750°C.
[0105] The present invention also provides the ceramic shell backing slurry described in any one of the above technical solutions, the ceramic shell backing slurry obtained by the preparation method described in any one of the above technical solutions, or the application of the ceramic shell described in any one of the above technical solutions in the preparation of single crystal blades.
[0106] In this invention, the application preferably includes applications that reduce or avoid recrystallization defects and / or thermal cracking problems on the surface of single-crystal blades, and more preferably applications that reduce or avoid recrystallization defects and thermal cracking problems on the surface of single-crystal blades.
[0107] In this invention, the preferred application includes reducing the residual strength of the ceramic shell and / or improving the high-temperature resilience of the ceramic shell, and more preferably, the application includes reducing the residual strength of the ceramic shell and improving the high-temperature resilience of the ceramic shell.
[0108] In this invention, the preferred method for removing the ceramic shell during the preparation of the single-crystal blades includes alkaline boiling.
[0109] This invention aims to complete and refine the overall technical solution, better ensure the composition and proportion of the ceramic shell backing layer slurry, and further improve the comprehensive performance of the ceramic shell backing layer. The aforementioned ceramic shell backing layer slurry for single-crystal blades and its preparation method, a ceramic shell for casting single-crystal blades, and its specific applications may include the following:
[0110] This invention provides a ceramic backing slurry for single-crystal blades and its preparation method. The slurry uses a silica sol binder and the refractory material is a mixed powder of fused white corundum, fused mullite and fused silica. The method includes the following steps: Step 1, ceramic powder preparation; Step 2, preparation of a mixed solution of binder and organic additives; Step 3, preparation of the backing slurry.
[0111] Furthermore, the present invention provides a ceramic shell backing slurry for single-crystal blades and a method for preparing it, comprising the following steps:
[0112] Step 1: Preparation of ceramic powder:
[0113] 1) Select fused white fused alumina powder, fused mullite powder and fused silica powder as shell backing powders, with fused white fused alumina powder accounting for 10-30%, fused mullite powder accounting for 70-90% and fused silica powder accounting for 0-10%.
[0114] 2) Weigh out appropriate amounts of fused white corundum, fused mullite and fused quartz powder according to the proportion, put them into a V-type mixer and mix them thoroughly. The mixer speed is 8-15 r / min and the mixing time is 30-60 min.
[0115] Step 2: Preparation of the adhesive and organic additive mixture solution:
[0116] 1) Select adhesives and organic additives; among which, organic additives include: wetting agents, defoamers, reinforcing agents, and thickeners;
[0117] 2) Take 0.3% to 0.9% of wetting agent, 0.3% to 0.9% of defoamer and 0.1% to 0.3% of thickener by volume of the adhesive and add them to the adhesive. Then weigh 5% to 10% of reinforcing agent by weight of the adhesive and add it to the adhesive to prepare a mixed solution. Turn on the mixer and stir for 5 to 10 minutes to obtain a mixed solution for later use.
[0118] Step 3: Preparation of backing slurry:
[0119] 1) Weigh the ceramic powder and the mixed solution according to the powder-to-liquid ratio of 2 to 4:1. While stirring, slowly add the ceramic powder to the mixed solution and stir in the mixer for 2 to 6 hours at a speed of 900 to 1500 r / min. During the stirring process, use cooling water to control the temperature of the mixing tank, and the temperature control range is 21 to 25℃.
[0120] 2) Use a diaphragm pump to transfer the prepared slurry to an L-shaped mixing tank and continue mixing for 48 to 72 hours;
[0121] 3) The specifications adopted are The viscosity of the slurry and the weight of the plate were tested using a flow cup viscometer and a 100×100mm wax plate. The slurry viscosity was adjusted to 10–25 s, and the plate weight was adjusted to 0.03–0.05 g / cm³. 2 The preparation of the backing slurry is complete.
[0122] Specifically, the particle size range of the fused white corundum powder is 0-0.12 mm, the particle size range of the fused mullite powder is 0-0.07 mm, and the particle size range of the fused silica powder is 0-0.15 mm.
[0123] Specifically, 0.1-0.3% thickener is added to the backing slurry for modification.
[0124] Specifically, the wetting agent is of type V12 or type 8M.
[0125] Specifically, the defoamer is n-octanol or Burst 100.
[0126] Specifically, the firing temperature for preparing the shell using this backing slurry should not exceed 800℃.
[0127] The present invention provides a ceramic shell backing slurry for single-crystal blades and its preparation method, a ceramic shell for casting single-crystal blades, and its application. The ceramic shell backing slurry for single-crystal blades, specially designed with a specific formula and composition, significantly improves the fluidity of the backing slurry while preventing thermal cracking and recrystallization caused by shell constraint in multi-unit single-crystal guide blades and crowned blades. By adjusting the particle size distribution and high-temperature performance of the ceramic powder, and by adding appropriate amounts of organic additives, the present invention achieves excellent fluidity and collapsibility. The residual strength of the shell prepared with this slurry can be reduced by more than 50%, meeting the requirements for use in multi-unit single-crystal guide blades and crowned blades.
[0128] This invention designs the shell material as a mixture of fused white corundum powder and fused mullite powder. The fused mullite is a standard 3Al2O3·2SiO2. During the directional solidification of the metal, the pre-added fused mullite acts as a seed crystal, promoting mullite formation and ensuring the high-temperature performance of the shell. The introduction of fused silica increases the SiO2 content of the entire shell system, improving the shell's collapse and yielding properties. Its residual strength is only 30% of that of pure fused white corundum shells and EC95 shells, alleviating the recrystallization tendency of multi-unit single-crystal guide vanes and crowned vanes. Moreover, the shell material can be removed by alkaline boiling, avoiding recrystallization of single-crystal vanes caused by physical removal.
[0129] This invention uses a mixture of fused white corundum, fused mullite, and fused silica powder as ceramic and refractory materials, silica sol as a binder, and appropriate organic additives to form a mixed solution. The process involves rapid stirring, stable stirring with an L-type mixer, and slurry adjustment. This invention optimizes the selection and particle size distribution of several ceramic powders and adds appropriate amounts of organic additives (wetting agents, defoamers, reinforcing agents, thickeners, etc.). In particular, the innovative introduction of thickeners significantly improves the coatability of the backing slurry. By combining the performance advantages of several ceramic powders in a specific ratio, the prepared shell exhibits excellent yielding properties, ensuring that the multi-unit single-crystal guide vanes and crowned blades do not suffer from residual stress due to excessive shell strength hindering metal shrinkage. This prevents recrystallization defects after heat treatment between multi-unit blades and at the blade / crown transition points, thus solving the surface recrystallization problem of multi-unit single-crystal guide vanes and crowned blades, and meeting the precision casting requirements for single-crystal turbine blades in aero-engines. Moreover, the preparation method is simple and easy to implement, the conditions are mild, the controllability is strong, and the stability is good, making it more suitable for industrial promotion and application.
[0130] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, describes a ceramic shell backing slurry for single-crystal blades and its preparation method, a ceramic shell for casting single-crystal blades, and its application. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures. They are only for further illustrating the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.
[0131] Example 1
[0132] A ceramic-type shell backing slurry for single-crystal blades was prepared. The process and steps are as follows:
[0133] Step 1: Preparation of ceramic powder:
[0134] 1) Select fused white fused alumina powder, fused mullite powder and fused silica powder as shell backing powders, with fused white fused alumina powder accounting for 20%, fused mullite powder accounting for 75% and fused silica powder accounting for 5%.
[0135] 2) Weigh out appropriate amounts of fused white corundum, fused mullite and fused quartz powder according to the proportion, put them into a V-type mixer and mix them thoroughly. The mixer speed is 10 r / min and the mixing time is 60 min.
[0136] Step 2: Preparation of the adhesive and organic additive mixture solution:
[0137] 1) Select binders and organic additives; the organic additives are: wetting agent V12 type, defoamer Burst100, reinforcing agent polyacrylic acid emulsion, and thickener associative polyurethane; the binder is GRJ-26 silica sol.
[0138] 2) Take 0.5% wetting agent, 0.5% defoamer and 0.1% thickener according to the volume of the adhesive and add them to the adhesive. Then weigh 8% reinforcing agent according to the weight of the adhesive and add it to the adhesive. Prepare a mixed solution, turn on the mixer and stir for 5 minutes to obtain a mixed solution for later use.
[0139] Step 3: Preparation of backing slurry:
[0140] 1) Weigh the ceramic powder and the mixed solution at a powder-to-liquid ratio of 3:1. While stirring, slowly add the ceramic powder to the mixed solution and stir in a mixer for 6 hours at a speed of 900 r / min. During the stirring process, use cooling water to control the temperature of the mixing tank, with a temperature control range of 22℃.
[0141] 2) Use a diaphragm pump to transfer the prepared slurry to an L-shaped mixing tank and continue mixing for 48 hours;
[0142] 3) The viscosity and plate weight of the slurry were tested using a φ6mm×100ml flow cup viscometer and a 100×100mm wax plate. The slurry viscosity was adjusted to 15s, and the plate weight was adjusted to 0.035g / cm³. 2 The preparation of the backing slurry is complete.
[0143] Example 2
[0144] A ceramic-type shell backing slurry for single-crystal blades was prepared. The process and steps are as follows:
[0145] Step 1: Preparation of ceramic powder:
[0146] 1) Select fused white fused alumina powder, fused mullite powder and fused silica powder as shell backing powders, with fused white fused alumina powder accounting for 15%, fused mullite powder accounting for 75% and fused silica powder accounting for 10%.
[0147] 2) Weigh out appropriate amounts of fused white corundum, fused mullite and fused quartz powder according to the proportion, put them into a V-type mixer and mix them thoroughly. The mixer speed is 15 r / min and the mixing time is 30 min.
[0148] Step 2: Preparation of the adhesive and organic additive mixture solution:
[0149] 1) Select binders and organic additives; the organic additives are: wetting agent 8M type, defoamer Burst100, reinforcing agent polystyrene-acrylic emulsion, and thickener hydroxymethyl cellulose; the binder is GRJ-26 silica sol.
[0150] 2) Take 0.3% wetting agent, 0.3% defoamer and 0.3% thickener by volume of the adhesive and add them to the adhesive. Then weigh 5% reinforcing agent by weight of the adhesive and add it to the adhesive to prepare a mixed solution. Turn on the mixer and stir for 10 minutes to obtain a mixed solution for later use.
[0151] Step 3: Preparation of backing slurry:
[0152] 1) Weigh the ceramic powder and the mixed solution according to the powder-to-liquid ratio of 2.4:1. While stirring, slowly add the ceramic powder to the mixed solution and stir in the mixer for 4.5 hours at a speed of 1000 r / min. During the stirring process, use cooling water to control the temperature of the mixing tank, and the temperature control range is 23℃.
[0153] 2) Use a diaphragm pump to transfer the prepared slurry to an L-shaped mixing tank and continue mixing for 72 hours;
[0154] 3) The viscosity and plate weight of the slurry were tested using a φ6mm×100ml flow cup viscometer and a 100×100mm wax plate. The slurry viscosity was adjusted to 12s, and the plate weight was adjusted to 0.03g / cm³. 2 The preparation of the backing slurry is complete.
[0155] Example 3
[0156] A ceramic-type shell backing slurry for single-crystal blades was prepared. The process and steps are as follows:
[0157] Step 1: Preparation of ceramic powder:
[0158] 1) Select fused white fused alumina powder, fused mullite powder and fused silica powder as shell backing powders, with fused white fused alumina powder accounting for 30%, fused mullite powder accounting for 70% and fused silica powder accounting for 0%.
[0159] 2) Weigh out appropriate amounts of fused white corundum and fused mullite powder according to the proportion, put them into a V-type mixer and mix them thoroughly. The mixer speed is 12 r / min and the mixing time is 45 min.
[0160] Step 2: Preparation of the adhesive and organic additive mixture solution:
[0161] 1) Select binders and organic additives; the organic additives are: wetting agent V12 type, defoamer n-octanol, reinforcing agent polystyrene-acrylic emulsion and polyethylene glycol (1:1 mixture), thickener hydroxymethyl starch; the binder is GRJ-30 silica sol.
[0162] 2) Take 0.8% wetting agent, 0.8% defoamer and 0.1% thickener according to the volume of the adhesive and add them to the adhesive. Then weigh 10% reinforcing agent according to the weight of the adhesive and add it to the adhesive to prepare a mixed solution. Turn on the mixer and stir for 10 minutes to obtain a mixed solution for later use.
[0163] Step 3: Preparation of backing slurry:
[0164] 1) Weigh the ceramic powder and the mixed solution according to the powder-to-liquid ratio of 3.5:1. While stirring, slowly add the ceramic powder to the mixed solution and stir in the mixer for 3 hours at a speed of 1400 r / min. During the stirring process, use cooling water to control the temperature of the mixing tank, and the temperature control range is 25℃.
[0165] 2) Use a diaphragm pump to transfer the prepared slurry to an L-shaped mixing tank and continue mixing for 60 hours;
[0166] 3) The viscosity and plate weight of the slurry were tested using a φ6mm×100ml flow cup viscometer and a 100×100mm wax plate. The slurry viscosity was adjusted to 20s, and the plate weight was adjusted to 0.04g / cm³. 2 The preparation of the backing slurry is complete.
[0167] The performance of the backing slurry prepared in Examples 1 to 3 of the present invention was tested.
[0168] See Table 1. Table 1 shows the parameters of the backing slurry prepared in Examples 1-3 of this invention and the traditional backing slurry, as well as the parameters for preparing the ceramic shell (comparison of viscosity and plate weight).
[0169] Table 1
[0170]
[0171] The foregoing has provided a detailed description of the ceramic shell backing slurry for single-crystal blades, its preparation method, a ceramic shell for casting single-crystal blades, and its applications. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the invention, including the best mode, and to enable any person skilled in the art to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. A ceramic-type shell backing slurry for single-crystal blades, characterized in that, Based on raw materials, it includes: a mixed solution consisting of binders and organic additives, and a powder consisting of ceramic powder; The ceramic powder comprises 10wt% to 30wt% of fused white corundum powder, 70wt% to 90wt% of fused mullite powder, and 0wt% to 10wt% of fused silica powder. The organic additives include one or more of wetting agents, defoamers, and reinforcing agents, as well as thickeners.
2. The ceramic shell backing slurry according to claim 1, characterized in that, The particle size of the fused white corundum powder is 0–0.12 mm; The particle size of the electrofused mullite powder is 0–0.07 mm; The particle size of the fused silica powder is 0–0.15 mm; The powder to the mixed solution mass ratio is (2-4):1; The flow cup viscosity of the ceramic shell backing slurry is 10–25 s.
3. The ceramic shell backing slurry according to claim 1, characterized in that, The amount of the reinforcing agent is 5% to 10% of the mass of the adhesive; The amount of the thickener is 0.1% to 0.3% of the volume of the binder; The amount of the wetting agent is 0.3% to 0.9% of the volume of the adhesive; The amount of the defoamer is 0.3% to 0.9% of the volume of the adhesive; The weight of the plate when the ceramic shell back layer slurry is coated is 0.03–0.05 g / cm³. 2 .
4. The ceramic shell backing slurry according to claim 1, characterized in that, The binder includes silica sol; The thickener includes one or more of associative polyurethane, hydroxymethyl cellulose, and hydroxymethyl starch; The wetting agent includes wetting agent type V12 and / or wetting agent type 8M; The defoamer includes n-octanol and / or defoamer Burst 100; The reinforcing agent includes one or more of polyacrylic acid emulsion, polystyrene-acrylic emulsion, and polyethylene glycol.
5. A method for preparing a ceramic shell backing slurry for single-crystal blades as described in any one of claims 1 to 4, characterized in that, Includes the following steps: 1) After mixing fused white corundum powder, fused mullite powder and fused quartz powder, ceramic powder is obtained; After the binder and organic additives are mixed again, a mixed solution is obtained; 2) After initial mixing and secondary mixing of the ceramic powder and the mixed solution obtained in the above steps, a ceramic shell backing slurry is obtained.
6. The preparation method according to claim 5, characterized in that, The mixing speed is 8–15 r / min; The mixing time is 30–60 minutes; The remixing time is 5–10 minutes; The remixing speed is 100-300 r / min; The initial mixing speed is 900–1500 r / min; The initial mixing time is 2–6 hours; The initial mixing temperature is 21–25°C; The secondary mixing time is 48h to 72h.
7. A ceramic shell for casting single-crystal blades, characterized in that, The back layer of the ceramic shell is obtained by preparing the ceramic shell back layer slurry according to any one of claims 1 to 4 or the ceramic shell back layer slurry obtained by the preparation method according to any one of claims 5 to 6.
8. The ceramic shell according to claim 7, characterized in that, The casting method includes precision casting; The single-crystal blades include multi-unit single-crystal guide blades and / or multi-unit single-crystal crowned blades; The preparation methods include coating and calcination; The roasting temperature is 650–800°C.
9. The application of the ceramic shell backing slurry according to any one of claims 1 to 4, the ceramic shell backing slurry obtained by the preparation method according to any one of claims 5 to 6, or the ceramic shell according to any one of claims 7 to 8 in the preparation of single-crystal blades.
10. The application according to claim 9, characterized in that, The applications include those that reduce or avoid recrystallization defects and / or thermal cracking problems on the surface of single-crystal blades; The application methods include reducing the residual strength of the ceramic shell and / or improving the high-temperature resilience of the ceramic shell; In the process of preparing single-crystal blades, the ceramic shell is removed by alkaline boiling.